Republic of South Sudan : 2014 Article IV Consultation-Staff Report; Staff Statement; and Press Release. (IMF Staff Country Reports; Country Report ;, 2014)
This 2014 Article IV Consultation highlights that South Sudan's economic performance has been mixed in recent years. Real GDP growth has displayed high volatility, the result of changes in oil and agricultural production. Inflation rose in an initial period of economic instability in 2011-12 but was contained in 2013-14 thanks to fiscal and monetary restraint and lower food prices. Serious challenges remain, including distortions in the foreign exchange market and in budget execution, lower international oil prices, and subdued oil production. As a result, financing the budget for FY2014/15 is challenging and will likely require policy decisions given the otherwise potentially adverse impact on economic stability and inflation.